2022
DOI: 10.1155/2022/4698656
|View full text |Cite
|
Sign up to set email alerts
|

Stock Trading Strategies Based on Deep Reinforcement Learning

Abstract: The purpose of stock market investment is to obtain more profits. In recent years, an increasing number of researchers have tried to implement stock trading based on machine learning. Facing the complex stock market, how to obtain effective information from multisource data and implement dynamic trading strategies is difficult. To solve these problems, this study proposes a new deep reinforcement learning model to implement stock trading, analyzes the stock market through stock data, technical indicators and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…In addition, the AR of Ref [51] is 55.71% on APPL, and our AR is also 7% higher than them. These results further explain MS-DDQN algorithm is more effective.…”
Section: ) Performance Analysismentioning
confidence: 40%
See 1 more Smart Citation
“…In addition, the AR of Ref [51] is 55.71% on APPL, and our AR is also 7% higher than them. These results further explain MS-DDQN algorithm is more effective.…”
Section: ) Performance Analysismentioning
confidence: 40%
“…We downloaded the source code from github and took the result with its highest AR a t the same time period. • Stock trading strategies based on deep reinforcement learning: Proposed by Li et al [51]. We directly took out the experimental results (AR) as baseline.…”
Section: Baseline Methodsmentioning
confidence: 99%
“…This study was conducted in response to the challenges and findings reported in the literature regarding the use of regression models to predict returns in financial stock markets. The authors of the reference article [1] suggested that regression models should not be used for this purpose, whereas the authors of [2] reported obtaining higher profits despite market inconsistencies. The present study aims to challenge these findings and develop a trading strategy based on a customized deep neural network (DNN) to predict returns in real time.…”
Section: A Problem Findingsmentioning
confidence: 99%
“…Researchers have integrated RL with deep neural networks, enabling the development of DRL methods for learning trading strategies from historical data. These approaches can be classified into three categories: value-based [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], policy-based [39][40][41][42][43][44], or actor-critic [45][46][47][48][49][50]. However, when it comes to generating trading strategies for sin-gle stock, the DRL algorithms primarily adopt value-based approaches.…”
Section: Drl In Financial Tradingmentioning
confidence: 99%
“…Ma et al developed a parallel multi-module DRL algorithm for stock trading, employing multiple neural networks and RL techniques to capture both current market data and long-term historical trends [29]. Li et al utilized a combination of Convolutional Neural Networks (CNN) and LSTM networks with Double DQN and Dueling DQN algorithms to learn optimal dynamic trading strategies from stock data and candlestick charts [33]. Taghian et al proposed a framework that integrated DQN with technical indicators to learn an optimal trading policy for individual assets [34].…”
Section: Drl In Financial Tradingmentioning
confidence: 99%